Religious-Based Family Management and Sustainable Household Consumption: Evidence from Indonesia - Hasmin, Hasmin; Nurung, Jumiaty (International Journal of Sustainable Energy Planning and Management, 2025)
Many low-income households in Indonesia face persistent economic vulnerability not merely due to income deprivation, but also due to behavioral and social constraints rooted in religious and kinship structures. This study investigates how Religious-Based Family Management (RBFM) and Silaturahim Quality (SQ)—two socially embedded institutions—affect household consumption behavior and sustainable resilience. Using a social feasibility approach, the study draws on primary data from 225 households and applies Structural Equation Modeling (SEM) to examine whether SQ mediates the influence of RBFM on the ability of households to maintain basic consumption while avoiding excessive resource depletion. Results demonstrate that RBFM significantly strengthens SQ, which in turn reduces economic precarity. These findings highlight the role of informal social systems as complementary mechanisms in achieving sustainable household energy transitions. Policy recommendations suggest empowering local value systems and integrating them into decentralized energy and consumption planning.